Lactate Dehydrogenase A as a Target of Cancer Therapy - Neolaka, Gladies Mercya Grameinie (Medicinus, 2023)
Lactate dehydrogenase (LDH) is an enzyme that catalyzes the conversion of pyruvate to lactate and on the contrary lactate to pyruvate. LDH is a tetramer consisting of two types of subunits M (LDHA) and H (LDHB). LDHA catalyzes the conversion of pyruvate to lactate, while LDHB converts lactate to pyruvate. LDHA increases its expression in cancer cells and is associated with cancer aggressiveness. Lactate that continues to increase gives the effect of an acidic microenvironment so that there is sufficient availability of oxygen for metabolism, which increases anaerobic glycolysis and decreases oxidative phosphorylation. Inhibition of LDHA can provide hope in cancer therapy because many studies have shown that inhibition of LDHA reduces cancer growth. This review will describe several cancer treatment approaches using LDH as a cancer therapy target until now.